STRATEGI GURU DALAM PEMANFAATAN MEDIA PEMBELAJARAN DI MASA PANDEMI DALAM MENINGKATKAN KEMAMPUAN KOGNITIF ANAK USIA DINI DI TK WARDA ARRIYADL - Bahari, Jon Iskandar (FKDP (Forum Komunikasi Dosen Peneliti), 2022)
A pandemic situation like this makes children not grow in increasing their cognitive intelligence. With the lack of parental knowledge and limited parental patience, it can affect children's learning outcomes so that children become bored and lazy to study so that the school develops children's cognitive abilities through environmental media and audio-visual media by means of online learning. This study aims to determine the teacher's strategy in using learning media during the pandemic in improving children's cognitive at Warda Arriyadl Jambewangi Kindergarten, to find out the advantages and disadvantages of learning media during the pandemic at Warda Arriyadl Jambewangi Kindergarten. This study used descriptive qualitative method. The subjects of the study were the principal, class teacher, students, and guardians of students at Warda Arriyadl Kindergarten Jambewangi. The place of research was carried out at Warda Arriyadl Kindergarten Dsn Jambewangi RT 03 RW 01 Jambewangi Sempu District. Data collection methods used are observation, interviews and documentation. Technical analysis of the data in this study is to collect data, data condensation, data presentation and drawing conclusions. The results of this study indicate that there is a development of children's cognitive abilities resulting from the method of utilizing the learning media.